Pembuatan Vertical Garden Botol Bekas Guna Penerapan P5 Di SDK Maumere 2, Kabupaten Sikka - Cornelia Hildegardis; Loko, Ignasius Reynaldi Leo; Putra, Annibale Mariano Paschalito Djogo; Soludale, Anastasia Merdekawati Noralita; El Puang, Desi Maria (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2024)
This Community Service Program (PKM) is motivated by the importance of plastic waste management and the implementation of the Pancasila Student Profile Strengthening Project (P5) at SDK Maumere 2, Sikka Regency. The goal of this activity is to educate students and teachers about the use of used bottles as the basic material for creating vertical gardens, in support of the P5 program, which focuses on environmental preservation and student creativity. The target partners for this activity are the teachers and students of SDK Maumere 2, with a total of 40 participants, consisting of 36 students and 4 teachers. The implementation method includes several stages: an introduction to the concept of vertical gardens, technical training on how to create vertical gardens using used bottles, and assistance during the process of making and installing them within the school environment. Qualitatively, this activity encourages students to be more creative and aware of environmental issues. It successfully contributes to the application of P5, enhances students' skills in utilizing recycled materials, and supports environmentally-oriented learning.